A clearing protocol for whole tissues: An example using haustoria of Orobanchaceae1. (2nd January 2013) - Morawetz, Jeffery J.
Abstract : Premise of the study: Due to lack of success in clearing whole tissues using only classical clearing techniques (e.g., Herr's 4½ solution, KOH, NaOH, lactic acid saturated with chloral hydrate), and because tissue degradation is often a result of harsh clearing agents (e.g., KOH, NaOH), a novel combined treatment was sought to improve the removal of obscuring tannins from intact haustoria. Methods and Results: Stockwell's bleach proved to be useful in removing tannins from haustoria, usually within 3 d (up to 10 d), rendering them opaque to (rarely) translucent. After bleaching, haustoria were successfully cleared in 1–3 d in a solution of lactic acid saturated with chloral hydrate at 42°C. Conclusions: The two‐step clearing protocol reported here will now facilitate structural studies on haustoria, such as those examining the presence and distribution of callose, and three‐dimensional reconstruction using confocal microscopy. Tissues in this study did not suffer from the degradation in quality observed using harsher treatments. This protocol should be useful for other difficult‐to‐clear tissues that are unable to be cleared using classical protocols alone.